Automatic documentation of users interactions with DICOM images: A case study in medical grand rounds - Bulcão-Neto, Renato F.; Camacho-Guerrero, José A.; Maced, Alessandra Alaniz (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2008: Anais do VIII Workshop de Informática Médica, 2008)
This paper presents a work in progress on automatic documentation of users interactions with digital medical images in DICOM format. As a proof of concept, we have developed a prototype application which automatically captures, registers and documents users interactions in a medical grand round scenario. The documentation resulting can aid medical professionals in several contexts of use, including decision taking processes, review of clinical cases, teaching and learning purposes, among others.